Numerical Calculation of Fracture Seepage in Rough Rock and Analysis of Local Pressure Drop - Gang Chen; Ling Ma; Hongsheng Gong; Fengqiang Luo (Geofluids)
The seepage performance of a rock mass mainly depends on the rock fractures developed in it. Numerical calculation method is a common method to study the permeability properties of fractures. Seepage in rock fractures is affected by various factors such as fracture aperture, roughness, and filling, among which aperture and roughness are the two most widely influenced factors. The Navier-Stokes (NS) equation can be solved directly for the seepage flow in rock fractures with good accuracy, but there are problems of large computational volume and slow solution speed. In this paper, the fracture aperture space data is substituted into the local cubic law as an aperture function to form a numerical calculation method for seepage in rough rock fractures, namely, the aperture function method (AFM). Comparing with the physical seepage experiments of rock fractures, the calculation results of AFM will produce a small amount of error under the low Reynolds number condition, but it can greatly improve the calculation efficiency. The high efficiency of calculation makes it possible to apply AFM to the calculation of large-scale 3D rough fracture network models. The pressure drop of fluid in the fracture has viscous pressure drop (VPD) and local pressure drop (LPD). VPD can be calculated using the AFM. After analyzing the results of solving the NS equation for fracture seepage, it is concluded that the LPD includes the pressure drop caused by area crowding in the recirculation zone (RZ), kinetic energy loss in the RZ, kinetic energy loss in the vortices, and other reasons.